Method for testing corrosion resistance of coating material formed part

By comparing the curved surface expansion treatment and strain distribution cloud diagram of standard samples of coated material, combined with salt spray box test, the accuracy of corrosion resistance determination of the plating material forming parts was solved, and high accuracy and repeatability were achieved test results of sexuality.

CN119322009APending Publication Date: 2025-01-17SHOUGANG JINGTANG IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411276350.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The prior art is difficult to accurately evaluate the corrosion resistance of coated material-shaped parts, especially under different deformation conditions, resulting in a low accuracy of measurement.

Method used

By performing curved surface expansion processing on standard samples of coated materials, recording the top punch height and expansion height, generating a strain distribution cloud map, and applying it to the corrosion samples to be tested, to compare the strain distribution cloud map of the target formed parts, and to determine Its corrosion resistance. At the same time, a salt spray box test is used to uniformly place the angle to improve the accuracy of the measurement.

Benefits of technology

Accurate measurement of corrosion resistance of formed parts of coated materials is achieved, avoiding the impact of the complexity and deformation of formed parts on the measurement, and improving the accuracy and repeatability of the measurement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119322009A_ABST
    Figure CN119322009A_ABST
Patent Text Reader

Abstract

The invention provides a method for testing the corrosion resistance of a coating material forming part, and belongs to the field of coating plate corrosion detection.The method comprises the steps that S1, the top punching height of a coating material standard sample is obtained; s2, according to the top punching height, the bulging height of the standard sample of the coating material is obtained; s3, obtaining a strain distribution cloud chart of the standard sample of the coating material at the bulging height; s4, obtaining a to-be-tested corrosion sample; s5, respectively obtaining strain distribution nephograms of a group of coating material standard samples and a group of corrosion samples to be tested; s6, comparing the strain distribution nephograms of the group of standard samples of the coating material with the strain distribution nephograms of the parts of the target forming part of the coating material; and S7, the corrosion resistance of all parts of the coating material target forming part is obtained. The method for measuring the forming limit curve of the coating and plating material is creatively applied to the corrosion resistance test of the coating and plating material forming part, so that the accuracy of measuring the corrosion resistance of the forming part is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of corrosion detection of coated plates, and in particular to a method for testing the corrosion resistance of parts formed of coated materials. Background Art

[0002] The coating includes zinc-aluminum-magnesium materials, pure zinc materials, etc. The zinc-aluminum-magnesium material is a ternary alloy coating whose main component is zinc, and the content of aluminum and magnesium is between 1.5% and 8% (the magnesium content is not less than 0.2%). Compared with traditional coatings such as hot-dip galvanizing, galvanized aluminum, zinc-iron alloy, etc., the coating has better corrosion resistance. The self-repair of the processing incision of the coated product means that in a humid and corrosive environment, the coating material near the incision dissolves into the water film attached to the exposed metal surface, and continuously migrates and infiltrates to the exposed incision position, forming a dense protective film (white rust) composed of zinc hydroxide, alkaline zinc chloride and magnesium hydroxide, which gradually covers the exposed incision metal, separates the external corrosive medium from the exposed metal matrix, and prevents the exposed incision from further corrosion. The whole process will last for a long time. The surface of the ZM plate is a complex structure composed of different phases, mainly including a binary eutectic phase composed of pure Zn phase, zinc-rich phase and MgZn2, and a ternary eutectic phase composed of Zn, MgZn2 and aluminum-rich phase.

[0003] The new type of coated alloy coating material has excellent atmospheric corrosion resistance and incision self-repairing performance, and can be used naked in the atmosphere after pre-galvanizing. After forming, the corrosion resistance of some parts with larger deformation will decrease to varying degrees. The currently widely used evaluation method is to conduct salt spray chamber tests after stamping the parts. However, this method is difficult to implement, and parts with different degrees of deformation have different corrosion resistance. It is impossible to evaluate the corrosion resistance under specific principal strain-secondary strain conditions, which leads to a low accuracy rate in the corrosion resistance measurement of parts formed by coated materials. Summary of the invention

[0004] The present application provides a method for testing the corrosion resistance of a part formed by a coated material, so as to solve the following technical problem: how to improve the accuracy of the corrosion resistance measurement of the part formed by the coated material.

[0005] The present application provides a method for testing the corrosion resistance of a formed part of a coated material, the method comprising:

[0006] S1. Performing a curved surface bulging process on a standard sample of a coating material having a first size, and obtaining a top height of the standard sample of the coating material when microcracks appear on the standard sample of the coating material;

[0007] S2. Obtaining the bulging height of the standard sample of the coating material according to the punch top height;

[0008] S3, obtaining a strain distribution cloud diagram of the standard sample of the coating material at the bulging height;

[0009] S4, performing a curved surface bulging process on a coating material to be tested sample having a first size at the bulging height to obtain a corrosion sample to be tested;

[0010] S5, repeating steps S1 to S4 for each standard sample of the coating material with other different set sizes, to obtain a set of strain distribution cloud diagrams of the standard sample of the coating material and a set of corrosion samples to be tested;

[0011] S6, comparing the strain distribution cloud diagrams of the set of standard samples of the coating material with the strain distribution cloud diagrams of the respective parts of the target formed part of the coating material, if the comparisons are consistent, the corrosion resistance of the standard sample of the coating material is consistent with that of the part of the target formed part of the coating material; and

[0012] S7. The corrosion resistance of each part of the target formed part of the coating material is obtained by the corrosion resistance of the set of standard samples of the coating material.

[0013] Optionally, the bulging height and the punching height satisfy the following relationship:

[0014] H1=n*H2,

[0015] Wherein, n is a constant, n≤1; H1 is the bulging height; H2 is the punching height.

[0016] Optionally, n is 0.85 to 0.90.

[0017] Optionally, the method for preparing the standard sample of the coating material includes:

[0018] Degreasing the coated material having a set size;

[0019] A white primer and a black dot paint are sequentially sprayed onto the surface of the degreased coating material.

[0020] Optionally, the degreasing is performed using an organic solvent.

[0021] Optionally, the organic solvent includes one or more of ethanol, acetone and methanol.

[0022] Optionally, the widths of the middle parallel sections of the standard samples of the coating material with different set sizes are 20 mm, 40 mm, 60 mm, 80 mm, 100 mm, 120 mm, 140 mm, 160 mm, and 180 mm, respectively.

[0023] Optionally, after step S7, the method further includes:

[0024] S8. placing a group of corrosion samples to be tested in a salt spray chamber at the same placement angle to perform a salt spray test, and obtaining a group of corrosion resistance data of the corrosion samples to be tested;

[0025] S9. Based on a set of corrosion resistance data of corrosion samples to be tested, corrosion resistance data of various parts of the target formed parts of the coating material are obtained.

[0026] Optionally, before step S8, the method further includes:

[0027] A group of corrosion samples to be tested were degreased and then edge-sealed.

[0028] Optionally, the edge sealing adopts 3M tape.

[0029] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0030] The present application provides a method for testing the corrosion resistance of a formed part of a coated material, comprising: S1, subjecting a standard sample of the coated material having a first size to a curved surface bulging process, and when microcracks appear on the standard sample of the coated material, obtaining a punching height of the standard sample of the coated material; S2, obtaining a bulging height of the standard sample of the coated material according to the punching height; S3, obtaining a strain distribution cloud diagram of the standard sample of the coated material at the bulging height; S4, subjecting a sample of the coated material to be tested having a first size to a curved surface bulging process at the bulging height to obtain a corrosion sample to be tested; S5, subjecting a sample of the coated material to be tested having a first size to a curved surface bulging process at the bulging height to obtain a corrosion sample to be tested; Repeat steps S1 to S4 for each standard sample of the coating material with different set sizes, and obtain a set of strain distribution cloud maps of the standard samples of the coating material and a set of corrosion samples to be tested; S6, compare the strain distribution cloud maps of each set of standard samples of the coating material with the strain distribution cloud maps of each part of the target formed part of the coating material. If the comparison is consistent, the corrosion resistance of the standard sample of the coating material is consistent with the part of the target formed part of the coating material; and S7, obtain the corrosion resistance of each part corresponding to the target formed part of the coating material through the corrosion resistance of the standard sample of the coating material. The present application creatively applies the method for determining the forming limit curve of the coating material to the corrosion resistance test of the formed part of the coating material. It avoids the problems caused by directly using the formed part to determine the corrosion resistance, can achieve a variety of different primary and secondary strain effects, the method is flexible, the results are highly repeatable, and the tested samples have corresponding primary and secondary strain maps. Thereby avoiding the influence of the complexity and deformation of the formed part on the corrosion resistance determination of the coating product, and improving the accuracy of the corrosion resistance determination of the formed part. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0033] Figure 1 A schematic flow chart of a method for testing the corrosion resistance of a formed part made of a coating material provided in an embodiment of the present application;

[0034] Figure 2 A preparation flow chart of the No. 1 corrosion sample to be tested and the standard sample of the coating material provided in the embodiment of the present application, and a strain distribution cloud diagram of the standard sample of the coating material;

[0035] Figure 3 The strain distribution cloud diagram of the corrosion sample No. 1 to be tested provided in the embodiment of the present application;

[0036] Figure 4 This is a picture of the No. 1 corrosion sample to be tested provided in the embodiment of the present application after 54 cycles of JASO M609 cyclic corrosion;

[0037] Figure 5 A preparation flow chart of the No. 5 corrosion sample to be tested and the standard sample of the coating material provided in the embodiment of the present application, and a strain distribution cloud diagram of the standard sample of the coating material;

[0038] Figure 6 The preparation flow chart of the No. 9 corrosion sample to be tested and the standard sample of the coating material provided in the embodiment of the present application, and the strain distribution cloud diagram of the standard sample of the coating material. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0040] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0041] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.

[0042] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0043] The inventive concept of this application is:

[0044] In the prior art, the method of evaluating whether the corrosion resistance of formed parts made of coated materials can meet the requirements of the parts is to place the formed parts made of coated materials in a salt spray chamber for corrosion resistance testing. However, the complexity and deformation of the formed parts have different effects on the corrosion resistance of the coated products. At the same time, there is no uniform placement angle for the formed parts in the salt spray chamber. Currently, there is no accurate method for measuring corrosion resistance.

[0045] The present application creatively applies the determination method of the forming limit curve of the coated material to the corrosion resistance test of the formed parts of the coated material. First, the first standard sample of the coated material is subjected to a curved surface bulging test. When cracks appear in the standard sample of the coated material, the bulging is stopped, and the height at this time is recorded as the punching height H2; then, at a bulging height of H1, a second standard sample of the coated material with the same size as the first standard sample of the coated material is subjected to a curved surface bulging test, and a surface strain distribution cloud map of the second standard sample of the coated material is collected, wherein the bulging height H1 is 0.85 to 0.90 of the punching height H2; then, at a bulging height of H1, a coated material to be tested sample with the same size as the first standard sample of the coated material is subjected to a curved surface bulging process to obtain a corrosion sample to be tested. Since the size and bulging height of the corrosion sample to be tested are the same as those of the second standard sample of the coated material, the surface strain distribution cloud map of the second standard sample of the coated material is equivalent to the surface strain distribution cloud map of the corrosion sample to be tested.

[0046] During the pressing and forming process of coated material formed parts, the strain distribution cloud map of each part of the coated material formed parts can be collected. Therefore, when the surface strain distribution cloud map of the corrosion sample to be tested is the same as the surface strain distribution cloud map of the specific part in the coated material formed part, it means that the forming conditions of the corrosion sample to be tested and the specific part in the coated material formed part are the same. During the forming process of the coated material, the thickness of the coated material will be thinned and the corrosion resistance will decrease. Therefore, to a certain extent, the corrosion resistance of the corrosion sample to be tested can also represent the corrosion resistance of the specific part in the coated material formed part.

[0047] At the same time, the present application prepares a group of standard samples of coated materials and corrosion samples to be tested, whose middle parallel section widths are 20mm, 40mm, 60mm, 80mm, 100mm, 120mm, 140mm, 160mm, and 180mm respectively. The surface strain distribution cloud map of the standard sample of the plated material thus obtained is a reference standard, which can include the strain distribution cloud map of each part of any same formed part of the coated material, so that the corrosion resistance of this group of corrosion samples to be tested can represent the corrosion resistance of each part of the formed part of the coated material. Finally, a group of corrosion samples to be tested are placed in a salt spray chamber, and the placement angles in the salt spray chamber are unified, and a salt spray test is carried out to obtain a group of corrosion resistance data of the corrosion samples to be tested, thereby obtaining the corrosion resistance data of each part of the formed part of the coated material. If the corrosion resistance of the corrosion sample to be tested is poor, the corrosion resistance of the corresponding part of the formed part of the coated material is also poor, and corresponding protective measures can be taken. The above method provided by the present application can use the corrosion resistance data of a set of corrosion samples to be tested for reference and reference to the corrosion resistance of any formed parts of the same material as the corrosion samples to be tested, so that the corrosion resistance can be measured without using the formed parts, and the weak corrosion resistance parts of the formed parts can be directly predicted. Therefore, the present application uses corrosion samples to be tested with different strains, which avoids the problems caused by directly using formed parts to measure the corrosion resistance, and can achieve a variety of different strain effects. The method is flexible and the results are highly repeatable. Thereby avoiding the influence of the complexity and deformation of the formed parts on the corrosion resistance measurement of the coating product, and improving the accuracy of the corrosion resistance measurement of the formed parts.

[0048] Figure 1 A schematic flow chart of a method for testing the corrosion resistance of a part formed of a coated material provided in an embodiment of the present application.

[0049] See also Figure 1 The present application provides a method for testing the corrosion resistance of a formed part of a coated material, the method comprising:

[0050] S1. Performing a curved surface bulging process on a standard sample of a coating material having a first size, and obtaining a top height of the standard sample of the coating material when microcracks appear on the standard sample of the coating material;

[0051] In some embodiments, the method for preparing the standard sample of the coating material includes:

[0052] Degreasing the coated material having a set size;

[0053] A white primer and a black dot paint are sequentially sprayed onto the surface of the degreased coating material.

[0054] In some embodiments, the degreasing is performed using an organic solvent.

[0055] In some embodiments, the organic solvent includes one or more of ethanol, acetone and methanol. The degreasing cannot use a degreasing liquid such as a strong alkali.

[0056] It should be noted that the specific method for measuring the punch top height is: use a rigid ball head to bulge the standard sample of the coated material. Once a crack appears on the sample, stop bulging and record the punch top height, so as to obtain an accurate limit range.

[0057] S2. Obtaining the bulging height of the standard sample of the coating material according to the punch top height;

[0058] In some embodiments, the bulging height and the punching height satisfy the following relationship:

[0059] H1=n*H2,

[0060] Wherein, n is a constant, n≤1; H1 is the bulging height; H2 is the punching height.

[0061] In some embodiments, n is 0.85-0.90.

[0062] In the above embodiment, the value of n can be any constant between 0.85 and 0.90, so as to avoid the sample cracking caused by excessive bulging height and to facilitate obtaining the strain range of the material during the actual stamping process. For example, the value of n can be 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, etc.

[0063] S3, obtaining a strain distribution cloud diagram of the standard sample of the coating material at the bulging height;

[0064] In some embodiments, the method for collecting the strain distribution cloud map of the standard sample of the coating material can be specifically: bulging the standard sample of the coating material at a height of n*H2, and after stopping the bulging, using a high-speed camera to collect information on the principal strain and secondary strain to obtain a strain distribution cloud map.

[0065] S4, performing a curved surface bulging process on a coating material to be tested sample having a first size at the bulging height to obtain a corrosion sample to be tested;

[0066] In some embodiments, the primer and spot paint on the surface of the standard sample of the coating material can be directly removed to directly obtain the corrosion sample to be tested.

[0067] S5, repeating steps S1 to S4 for each standard sample of the coating material with other different set sizes, to obtain a set of strain distribution cloud diagrams of the standard sample of the coating material and a set of corrosion samples to be tested;

[0068] In some embodiments, the widths of the middle parallel sections of the standard samples of the coating material with different set sizes are 20 mm, 40 mm, 60 mm, 80 mm, 100 mm, 120 mm, 140 mm, 160 mm, and 180 mm, respectively.

[0069] S6, comparing the strain distribution cloud diagrams of the set of standard samples of the coating material with the strain distribution cloud diagrams of the respective parts of the target formed part of the coating material, if the comparisons are consistent, the corrosion resistance of the standard sample of the coating material is consistent with that of the part of the target formed part of the coating material; and

[0070] S7. The corrosion resistance of each part of the target formed part of the coating material is obtained by the corrosion resistance of the set of standard samples of the coating material.

[0071] In some embodiments, after step S7, the method further comprises:

[0072] S8. placing a group of corrosion samples to be tested in a salt spray chamber at the same placement angle to perform a salt spray test, and obtaining a group of corrosion resistance data of the corrosion samples to be tested;

[0073] S9. Based on a set of corrosion resistance data of corrosion samples to be tested, corrosion resistance data of various parts of the target formed parts of the coating material are obtained.

[0074] In some embodiments, before step S8, the method further includes: degreasing a group of corrosion samples to be tested respectively, and then performing edge sealing.

[0075] In some embodiments, the edge sealing is performed using 3M tape.

[0076] In the implementation of the present application, on the one hand, a group of corrosion samples to be tested can be prepared at the same time, and the strain distribution cloud map of this group of corrosion samples to be tested can correspond to the strain distribution cloud map of each part of the target formed part, so that the corrosion resistance of the corrosion samples to be tested corresponds to the corrosion resistance of each part of the target formed part, and at the same time, this group of corrosion samples to be tested is placed in a salt spray chamber for corrosion resistance testing at a uniform placement angle, so that the corrosion resistance of all parts of the target formed part can be known, and corresponding adjustments can be made for parts with poor corrosion resistance to improve corrosion resistance, which has a certain reference role in the subsequent corrosion protection of the formed parts. On the other hand, corrosion samples to be tested can also be prepared for parts of the target formed part where the coating is thinned, so as to know the corrosion resistance of specific parts of the target formed part.

[0077] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0078] This embodiment provides a method for testing the corrosion resistance of a formed part of a coating material, the method comprising:

[0079] The present application provides a method for testing the corrosion resistance of a formed part of a coated material, the method comprising:

[0080] S11. Process the DX51D+ZM brand sample into the size required for FLC bulging (the width of the middle parallel section is the set size), process three samples, and perform two painting processes on sample one and sample two after degreasing, first spray white primer, and then spray black dot paint, to obtain the first coating material standard sample and the first coating material standard sample, respectively. Sample three is used to prepare the corrosion sample to be tested. Perform curved surface bulging on the coating material standard sample with the first size, and when microcracks appear on the coating material standard sample, obtain the top height of the coating material standard sample;

[0081] S21, obtaining the bulging height of the standard sample of the coating material according to the punching height;

[0082] S31, obtaining a strain distribution cloud diagram of the standard sample of the coating material at the bulging height;

[0083] S41, performing a curved surface bulging process on a coating material to be tested sample having a first size at the bulging height to obtain a corrosion sample to be tested;

[0084] S51, repeating steps S1 to S4 for each standard sample of the coating material with other different set sizes, to obtain a set of strain distribution cloud diagrams of the standard sample of the coating material and a set of corrosion samples to be tested;

[0085] S61, comparing the strain distribution cloud diagrams of the set of standard samples of the coating material with the strain distribution cloud diagrams of the respective parts of the target formed part of the coating material, if the comparisons are consistent, the corrosion resistance of the standard sample of the coating material is consistent with that of the part of the target formed part of the coating material; and

[0086] S71, obtaining the corrosion resistance of each part of the target formed part of the coating material by the corrosion resistance of the set of standard samples of the coating material;

[0087] S81, placing a group of corrosion samples to be tested in a salt spray chamber at the same placement angle to perform a salt spray test, and obtaining a group of corrosion resistance data of the corrosion samples to be tested;

[0088] S91. Based on the corrosion resistance data of a group of corrosion samples to be tested, the corrosion resistance data of each part of the target formed part of the coated material is obtained. The parameters of the method for testing the corrosion resistance of the formed part of the coated material are shown in Table 1.

[0089] Table 1 Parameters of the method for testing the corrosion resistance of formed parts of coated materials

[0090]

[0091]

[0092] Figure 2 A preparation flow chart of the No. 1 corrosion sample to be tested and the standard sample of the coating material provided in the embodiment of the present application, and a strain distribution cloud diagram of the standard sample of the coating material; Figure 5 A preparation flow chart of the No. 5 corrosion sample to be tested and the standard sample of the coating material provided in the embodiment of the present application, and a strain distribution cloud diagram of the standard sample of the coating material; Figure 6 The preparation process of the corrosion specimen No. 9 to be tested and the standard specimen of the coating material provided in the embodiment of the present application, and the strain distribution cloud diagram of the standard specimen of the coating material. For the specific preparation process of the corrosion specimen No. 1, No. 5 and No. 9 to be tested and the standard specimen of the coating material, and the strain distribution cloud diagram of the standard specimen of the coating material, please refer to Figure 2 , 5 and 6. The strain distribution cloud diagram of the standard sample of the coating material can correspond to the strain distribution cloud diagram of a specific part in any target formed part, so that the corrosion resistance test result of the corrosion sample to be tested can correspond to the corrosion resistance of the specific part in the target formed part.

[0093] Figure 4 This is a picture of the No. 1 corrosion sample to be tested provided in the embodiment of the present application after 54 cycles of JASO M609 cyclic corrosion; Figure 4 It can be seen that the surface corrosion of the corrosion sample to be tested is serious, indicating that the corrosion resistance of the specific parts of the parts corresponding to the corrosion sample to be tested is poor, and subsequent protection measures should be taken.

[0094] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for testing the corrosion resistance of a formed part of a coated material, characterized in that: The method comprises: S1. Performing a curved surface bulging process on a standard sample of a coating material having a first size, and obtaining a top height of the standard sample of the coating material when microcracks appear on the standard sample of the coating material; S2. Obtaining the bulging height of the standard sample of the coating material according to the punch top height; S3, obtaining a strain distribution cloud diagram of the standard sample of the coating material at the bulging height; S4, performing a curved surface bulging process on a coating material to be tested sample having a first size at the bulging height to obtain a corrosion sample to be tested; S5, repeating steps S1 to S4 for each standard sample of the coating material with other different set sizes, to obtain a set of strain distribution cloud diagrams of the standard sample of the coating material and a set of corrosion samples to be tested; S6, comparing the strain distribution cloud diagrams of the set of standard samples of the coating material with the strain distribution cloud diagrams of the respective parts of the target formed part of the coating material, if the comparisons are consistent, the corrosion resistance of the standard sample of the coating material is consistent with that of the part of the target formed part of the coating material; and S7. The corrosion resistance of each part of the target formed part of the coating material is obtained by the corrosion resistance of the set of standard samples of the coating material.

2. The method according to claim 1, characterized in that The bulging height and the punching height satisfy the following relationship: H1=n*H2, Wherein, n is a constant, n≤1; H1 is the bulging height; H2 is the punching height.

3. The method according to claim 2, characterized in that n is 0.85~0.

90.

4. The method according to claim 1, characterized in that: The method for preparing the standard sample of the coating material comprises: Degreasing the coated material having a set size; A white primer and a black dot paint are sequentially sprayed onto the surface of the degreased coating material.

5. The method according to claim 4, characterized in that The degreasing adopts an organic solvent.

6. The method according to claim 5, characterized in that The organic solvent includes one or more of ethanol, acetone and methanol.

7. The method according to claim 1, characterized in that The widths of the middle parallel sections of the standard samples of the coating material with different set sizes are 20mm, 40mm, 60mm, 80mm, 100mm, 120mm, 140mm, 160mm and 180mm respectively.

8. The method according to claim 1, characterized in that After step S7, the method further comprises: S8, placing the group of corrosion samples to be tested in a salt spray chamber at the same placement angle to perform a salt spray test to obtain corrosion resistance data of the group of corrosion samples to be tested; S9. Based on a set of corrosion resistance data of corrosion samples to be tested, corrosion resistance data of various parts of the target formed parts of the coating material are obtained.

9. The method according to claim 8, characterized in that Before step S8, the method further comprises: A group of corrosion samples to be tested were degreased and then edge-sealed.

10. The method according to claim 9, characterized in that The edge sealing adopts 3M tape.